Improving Activities and Writing Skill in English Simple Descriptive Text by Applying the Strategy of the Picture Word Inductive Model in Students of Class VIID Warureja Junior High School in the Academic Year 2017/2018: Array - Subektiningsih Subektiningsih (Dialektika Jurnal Pendidikan, 2019)
Increase in activity in writing simple descriptive texts in English by applying the picture word inductive model strategy to students in class VII D Warureja Junior High School 2 in the 2017/2018 school year and increasing the skills of writing simple descriptive texts in English by applying inductive picture word strategies model on students of class VII D Warureja Junior High School 2017/2018 school year. The study was conducted in 2 cycles using an action research model consisting of four components, namely planning, implementing, observing and reflecting. The research subjects were students of class VII D of Warureja Junior High School 2 in the academic year 2017/2018 with 29 students consisting of 15 male students and 14 female students. The conclusions from the results of this class action research are the application of the picture word inductive model strategy that can increase the activity of writing simple descriptive text in English by 10.35%, that is, from the first cycle of 55.17% with the criteria active enough to be 65.52% in cycle 2 active criteria and the application of picture word inductive model strategies can improve simple descriptive text writing skills in English by 10.34%, namely in cycle 1 of 68.97% increasing to 79.31% in cycle 2.